The effect of milling time on magnetite (Fe3O4) crystal structure made from volcanic minerals gathered from Mount Marapi, West Sumatra - Maya Sri Anggraini; Ramli Ramli; Hidayati Hidayati (Department of Physics – Universitas Negeri Padang UNP, 2017)
Indonesia is one of the archipelago countries rich in the abundant natural resources potential one of them is iron sand. Iron sand can be found in Mount Marapi located in West Sumatera Indonesia.Gunung is classified as the active volcano in Sumatra located in the district Agam. The existence of iron sand is only in the exploitation in the raw state (raw material) so it has a high selling value that is by knowing its characteristics. The characteristics of iron sand based on Crystal structure, the size of crystals and know the magnetite elements of iron sand that exist in the region Agam regency. This research is a type of experimental research conducted in the Materials Laboratory of Physics Department. In this study variations were performed on milling time. X-Ray Diffraction (XRD) is used to identify the phase, structure and size of crystals. X-Ray Fluorescence (XRF) is used to obtain data of magnetite content in iron basest before and after milling. In this study obtained XRD test data that due to increased time milling phase changes from hematite to magnetite. The increasing variation in milling time causes the change of magnetite structure from cubic structure to cubic structure. Increased milling time, magnetite crystal size increases up to a certain milling time and then decreases. As in the magnetite crystals before dimilling, 1.08 nm, after dimilling with 25 hours, 30 hours, 35 hours and 40 hours variations were obtained at 1.14 nm, 1.20 nm, 1.23 nm and 1.61 nm respectively. Furthermore, there was a decrease in the variation of mill-ing time of 45 hours obtained by 1.29 nm